Modelagem do efeito Raman espontâneo para sensoriamento distribuído de temperatura - Silva, Luís Cicero Bezerra da (2017)
The spontaneous Raman scattering is an effect caused by the interaction of an electromagnetic field with the molecules of the medium of propagation. This effect is strongly temperature dependent, finding therefore, applications in sensing. In this work, this effect observed in optical fibers is modeled for using in distributed temperature sensing. At first, a review over already studied and reported DTS was carried out, which provided the basic parameters to our analysis. After obtaining such parameters, the equations to reproduce the spontaneous Raman effect were implemented using the software Matlab. Once defined the proposed sensor model, simulations were performed. Various parameters and settings have been extensively analyzed with the purpose of studying how these parameters affect the sensor performance. Special attention was given to the processing of the backscattered signal since it carries the information of temperature along the fiber. The sensor performance was verified through its operation range, spatial resolution and temperature. This study provides fundamental principles of how to design distributed temperature sensors in optical fibers based on spontaneous Raman scattering. Also, it presents an optimized approach to developing sensors that meet the industry’s need, especially in the monitoring of large structures, where knowledge of abrupt changes of temperature is critical in preserving the structures and mainly the security of persons working in such places